2021
DOI: 10.1093/bjs/znab035
|View full text |Cite
|
Sign up to set email alerts
|

A meta-epidemiological study of bias in randomized clinical trials of open and laparoscopic surgery

Abstract: Background Blinding, random sequence generation, and allocation concealment are established strategies to minimize bias in RCTs. Meta-epidemiological studies of drug trials have demonstrated exaggerated treatment effects in RCTs where such methods were not employed. As blinding is more difficult in surgical trials it is important to determine whether this applies to them. The study aimed to investigate this using systematic meta-epidemiological methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Twenty-three studies addressed the effects of blinding of outcome assessors/adjudicators (30, 33-35, 37-39, 41, 42, 44, 51-53, 55, 57, 58, 61-63, 71-73).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-three studies addressed the effects of blinding of outcome assessors/adjudicators (30, 33-35, 37-39, 41, 42, 44, 51-53, 55, 57, 58, 61-63, 71-73).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies addressed the effects of blinding of patients (31, 33-35, 41, 44, 47, 48, 55, 62, 71, 73).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical heterogeneity was due to a need for additional calculations based on the data as described in the Methods and summarized in the eAppendix in Supplement 1. While participant masking is an unavoidable limitation in prehabilitation studies, as participants cannot be masked to their exercise intervention, assessor masking was not mentioned in 4 of the 12 studies, potentially limiting the assessment of clinical outcomes . For these reasons, when using GRADE, we determined the certainty of the evidence to be moderate (for V̇ o 2 peak and complications) to very low for our outcomes (eTable 4 in Supplement 1).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is the potential impact of lack of blinding on iSSI results. A review of blinding in surgical RCTs comparing laparoscopic and open surgery showed a significant reduction in the differences in length of stay and complications when participant or assessor blinding was achieved [30]. While patient blinding is not possible with MBP, assessor blinding can still be achieved.…”
Section: Discussionmentioning
confidence: 99%